Experiencing Globalization: Religion in Contemporary Contexts - Nault, Derrick M. (Key Issues in Modern Sociology, 2013)
This collection of essays, with special reference to Asia, analyzes religion through lived experience and reveals how religious phenomena are inextricably linked to globalizing processes.